Employee Performance Accountability Target Indicators - Ade Hermawan; Abd. Rohman; Riky Welli Saputra (East Asian Journal of Multidisciplinary Research, 2022)
This study uses an evaluation method with a quantitative descriptive approach, with some respondents being State Civil Apparatuses who had received the services of the Personnel, Education and Training Agency (BKPP). The secondary data uses the Banjarbaru City BKPP performance report document. The information and facts obtained are then read, analyzed, and interpreted to draw conclusions. The results showed that the accountability of the performance of the Banjarbaru City BKPP was that the Performance Accountability of the Banjarbaru City Personnel, Education and Training Agency in general tended to be good as measured by two main indicators, namely the arrangement of personnel resources and the quality of personnel administration services. The indicator of the arrangement of personnel resources is measured using three items. The indicator of the arrangement of personnel resources is measured using three items. The indicator of the arrangement of personnel resources is measured using three items.